2013
DOI: 10.1128/jvi.01634-12
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein Kinase Is Required for the Macropinocytic Internalization of Ebolavirus

Abstract: c Identification of host factors that are needed for Zaire Ebolavirus (EBOV) entry provides insights into the mechanism(s) of filovirus uptake, and these factors may serve as potential antiviral targets. In order to identify novel host genes and pathways involved in EBOV entry, gene array findings in the National Cancer Institute's NCI-60 panel of human tumor cell lines were correlated with permissivity for EBOV glycoprotein (GP)-mediated entry. We found that the gene encoding the ␥2 subunit of AMPactivated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 91 publications
1
36
0
Order By: Relevance
“…KSHV entry into cells is primarily through clathrin-mediated endocytosis in HUVEC and fibroblasts (34,46) and macropinocytosis in dermal microvascular endothelial cells (DMVEC) (47). Because other reports showed that AMPK activation enhanced macropi- nocytosis (14,15), we examined the role of AMPK activation on KSHV entry and infection. We found that inhibition of AMPK activation by either AMPK␣1 knockdown or the use of inhibitor compound C did not affect KSHV entry and trafficking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KSHV entry into cells is primarily through clathrin-mediated endocytosis in HUVEC and fibroblasts (34,46) and macropinocytosis in dermal microvascular endothelial cells (DMVEC) (47). Because other reports showed that AMPK activation enhanced macropi- nocytosis (14,15), we examined the role of AMPK activation on KSHV entry and infection. We found that inhibition of AMPK activation by either AMPK␣1 knockdown or the use of inhibitor compound C did not affect KSHV entry and trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…Several other RNA viruses, including Sindbis virus (SINV), vesicular stomatitis virus (VSV), and Kunjin virus (KUNV), which depend on cellular membrane modifications and fatty acid synthesis, are also restricted by AMPK (13). In contrast to RNA viruses, DNA viruses Zaire Ebolavirus and vaccinia virus rely on the AMPK activity for actin polymerization and the induction of macropinocytosis during entry (14,15).…”
mentioning
confidence: 99%
“…Molecular modeling studies using the crystal structure of EBOV GP as well as mutational analysis suggest a hydrophobic pocket at or near the interface of GP1 and GP2 as a hypothetical binding site for compound 11 (Basu et al, 2011). The AMP-activated protein kinase (AMPK) inhibitor, dorsomorphin (12), has been demonstrated to inhibit Ebola virus entry and infection in vitro, indicating role of host AMPK in EBOV infection and its potential as a target for antiviral drug development (Kondratowicz et al, 2013). p38 MAP kinase is also thought to play an important role in EBOV entry since inhibitors of the enzyme have been demonstrated to impair viral entry in human dendritic cells .…”
Section: Viral Entry Inhibitorsmentioning
confidence: 99%
“…The National Cancer Institute-60 (NCI-60) panel consists of 59 distinct cell lines with well-characterized transcriptomic profiles (Shankavaram et al, 2007;Weinstein and Pommier, 2003). The diversity of cell types and the depth of transcriptomic data permit high confidence genome-wide correlations between cellular gene expression and infection susceptibility (Kondratowicz et al, 2013;Lenaerts et al, 2012;Schowalter et al, 2012). We therefore inoculated the NCI-60 panel of cell lines with a singlecycle variant of A/WSN/1933 (H1N1, WSN) encoding GFP (WSN-GFP) ( Figure 1A).…”
Section: Gene Correlation Analysis Identifies Putative Enhancers and mentioning
confidence: 99%